The Influence Facilities Towards Teaching Method at MAS Al-Jam’iyatul Washliyah Tebing Tinggi - Balqis Fadiah; Lainatusshifa; Rizki Adha; Putri Maulida; Emeliya Sukma Dara (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2022)
This study aims to determine, provide a complete and clear picture of the influence of school facilities and infrastructure on the learning process of Mas Al Jam'iyatul Washliyah high cliff students. This research was conducted on level 3 senior high school students in the academic odd semester of 2022/2023. The research methods used in this research are quantitative methods, library research, and quantitative methods. Data collection techniques through direct observation to schools, distributing questionnaires containing several questions and conducting interviews with several teachers, the results obtained from this study are: 1) the school has enough facilities that support the learning process. The most of the students agree that the school has complete facilities that support the learning process. 2) 75% of the total 100%, only about 25% do not agree that the facility is a bad influence. 3) Some teachers do not use school facilities properly so that the existing facilities are not used. 4) There are more students who like the way teacher uses the facility in learning process than do not like it. Those who like it because of the teacher is creative in using the facility.